Advance care planning for nursing home residents with dementia: policy vs. practice. (12th November 2015) - Ampe, Sophie; Sevenants, Aline; Smets, Tinne; Declercq, Anja; Van Audenhove, Chantal
Abstract: Aims: The aims of this study were: to evaluate the advance care planning policy for people with dementia in nursing homes; to gain insight in the involvement of residents with dementia and their families in advance care planning, and in the relationship between the policy and the actual practice of advance care planning. Background: Through advance care planning, nursing home residents with dementia are involved in care decisions, anticipating their reduced decision‐making capacity. However, advance care planning is rarely realized for this group. Prevalence and outcomes have been researched, but hardly any research has focused on the involvement of residents/families in advance care planning. Design: Observational cross‐sectional study in 20 nursing homes. Methods: The ACP audit assessed the views of the nursing homes' staff on the advance care planning policy. In addition, individual conversations were analysed with 'ACP criteria' (realization of advance care planning) and the 'OPTION' instrument (involvement of residents/families). Data collection: June 2013–September 2013. Results: Nursing homes generally met three quarters of the pre‐defined criteria for advance care planning policy. In almost half of the conversations, advance care planning was explained and discussed substantively. Generally, healthcare professionals only managed to involve residents/families on a baseline skill level. There were no statistically significant correlations between policy and practice. Conclusion: The evaluations of the policy were promising, but the actual practice needs improvement. Future assessment of both policy and practice is recommended. Further research should focus on communication interventions for implementing advance care planning in the daily practice.